OP0307 A NOVEL TARGETED APPROACH TO ACHIEVE IMMUNE SYSTEM RESET: CD45-TARGETED ANTIBODY DRUG CONJUGATES AMELIORATE DISEASE IN PRECLINICAL AUTOIMMUNE DISEASE MODELS AND ENABLE AUTO-HSCT. (2nd June 2020) - Gillard, G.; Proctor, J.; Hyzy, S.; Mikse, O.; Lamothe, T.; Mcdonough, S.; Clark, N.; Palchaudhuri, R.; Bhat, A.; Brooks, M.; Sarma, G.; Bhattarai, P.; et al.
Abstract : Background: Resetting the immune system through autologous hematopoietic stem cell transplant (autoHSCT) is a highly effective treatment in selected patients with autoimmune diseases. AutoHSCT can induce long-term remission with 80% progression free survival in multiple sclerosis patients (Muraro 2017, Burt 2019). Use of autoHSCT in scleroderma patients has achieved superior outcomes in two randomized studies compared to standard of care (Tyndall 2014, Sullivan 2018). These impressive results are achieved by a combination of the eradication of autoreactive immune effector cells and re-establishment of self-tolerance, i.e., immune system reset. However, only a small fraction of eligible patients undergo autoHSCT, largely due to toxicity associated with current conditioning protocols. Objectives: As part of our goal to enable more patients to benefit from immune system reset, we have generated novel anti-human CD45 ADCs that cross react with nonhuman primates (NHP) and an anti-mouse CD45 ADC to model the approach in mouse models of AID. Methods: The human-targeted CD45-ADC is an affinity-matured mAb that targets an epitope present on all human CD45 isoforms, is cross-reactive with NHP CD45, and is conjugated to a payload that efficiently kills both quiescent and cycling cells. This ADC is engineered to eliminate Fc-mediated effector function, enable site-specific conjugation of linker/payload, and enable rapid clearance. This ADC was evaluated in vitro and in vivo in hNSG and NHPs. The murine tool ADC specifically targets the CD45.2 isoform of mouse CD45, and is also engineered to eliminate effector function, allow for site-specific conjugation of linker payload, and be rapidly cleared. The payload for this murine tool ADC is potent and preferentially kills dividing cells. This ADC was tested for the ability to enable immune reset and ameliorate autoimmune disease in multiple disease models. Results: The anti-human CD45-ADC showed efficient killing of human HSCs and human and cyno PBMC, including CD3 + cells from healthy donors and patients with MS. In hNSG, single doses of the CD45-ADC were well-tolerated and led to substantial depletion of human cells. In NHPs, single doses of CD45-ADC were well tolerated and depleted both peripheral lymphocytes and HSCs. Administration of a single dose of anti-human CD45-ADC to hNSGs with sclerodermatous xenoGVHD resulted in depletion of human T cells and resolution of symptoms. A single-dose of the anti-mouse CD45-ADC enabled full myeloablation and complete durable donor chimerism with congenic HSCT at 16 weeks. In a murine immunization model of MS, MOG-induced EAE, a single dose of the CD45-ADC followed by congenic HSCT prior to disease onset enabled full donor chimerism, significantly delayed disease onset and reduced disease severity. We are generating additional data in an adoptive transfer model of EAE to confirm and extend these results. In a murine model of arthritis, therapeutic treatment with a single dose of the CD45-ADC followed by congenic HSCT enabled complete donor chimerism and halted disease progression, comparable to with the effects of an anti-TNFα antibody. The ADC is being further evaluated in a model of type 1 diabetes and those data will be presented. These data demonstrate that CD45-ADC conditioning followed by congenic HSCT is sufficient for full myeloablation and immune reset. Conclusion: These results demonstrate that targeted immune depletion with a single dose of CD45-ADC can enable auto-HSCT and immune reset in multiple AID indications without toxic side effects. Targeted conditioning with CD45-ADC may represent a better tolerated approach for removing disease-causing cells as part of immune reset through auto-HSCT and enable more patients to benefit. Disclosure of Interests: Geoffrey Gillard Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Jennifer Proctor Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Sharon Hyzy Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Oliver Mikse Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Tahirih Lamothe Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Sean McDonough Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Nicholas Clark Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Rahul Palchaudhuri Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Anjali Bhat Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Melissa Brooks Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Ganapathy Sarma Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Prashant Bhattarai Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Pranoti Sawant Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Brad Pearse Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Charlotte McDonagh Shareholder of: Magenta Therapeutics, Employee of: Magenta Therapeutics, Tony Boitano Shareholder of: Magenta, Employee of: Magenta, Michael Cooke Shareholder of: Magenta, Employee of: Magenta